2019
DOI: 10.1515/witt-2019-0010
|View full text |Cite
|
Sign up to set email alerts
|

Hinges, Prejudices, and Radical Doubters

Abstract: This paper makes use of the Wittgenstein-inspired perspective of hinge epistemology in connection with research on epistemic injustice. Its aim is to shed light on the neglected relationship between hinges and prejudices, by focussing on the role of the “radical doubter” in epistemic practices. After the introduction, section 1 presents Miranda Fricker’s (2007) seminal work and points out that epistemic injustice typically involves the silence of discriminated groups, an aspect that emerges with most clarity w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Its principal aim, to date, has been the development of an antiskeptical strategy based on the acknowledgment of the unwarrantability of hinges (Coliva 2015;Coliva and Moyal-Sharrock 2016;Pritchard 2016;Schönbaumsfeld 2016). However, the significance of the Wittgensteinian intuition goes much beyond this and proves particularly helpful in social epistemology, as more recent research has shown (Ashton 2019;Boncompagni 2019;Coliva 2019a, Forthcoming; see also Greco 2016;O'Hara 2018;Ranalli 2018;Coliva and Palmira 2020, Forthcoming).…”
Section: A Proposal: the Hinge Accountmentioning
confidence: 99%
See 1 more Smart Citation
“…Its principal aim, to date, has been the development of an antiskeptical strategy based on the acknowledgment of the unwarrantability of hinges (Coliva 2015;Coliva and Moyal-Sharrock 2016;Pritchard 2016;Schönbaumsfeld 2016). However, the significance of the Wittgensteinian intuition goes much beyond this and proves particularly helpful in social epistemology, as more recent research has shown (Ashton 2019;Boncompagni 2019;Coliva 2019a, Forthcoming; see also Greco 2016;O'Hara 2018;Ranalli 2018;Coliva and Palmira 2020, Forthcoming).…”
Section: A Proposal: the Hinge Accountmentioning
confidence: 99%
“…However, what might happen next, and this marks the second level of the emergence of hinges, is that the hinge becomes questionable and finally is questioned. Radical doubts of it become conceivable, and radical doubters start to be listened to (Boncompagni 2019). This makes the hinge vulnerable: the reasons behind it might finally be examined.…”
mentioning
confidence: 99%
“…Feminist epistemology and philosophy of science have drawn on Wittgensteinian ideas on "objectivity", epistemology and language in order to interrogate the problem of male (and other) bias in the production of knowledge (cf. Diamond 1991, Crary 2001, Boncompagni 2019, Ashton 2019. The Wittgensteinian investigation of scepticism has been explored in order to show the social and gendered production of doubt, loss of confidence or difficulty in expressing in words what is experienced as violence (cf.…”
mentioning
confidence: 99%